Dietary supplementation of coated sodium butyrate improves growth performance of laying ducks by regulating intestinal health and immunological performance - Zeng, Tao; Sun, Hanxue; Huang, Manman; Guo, Rongbing; Gu, Tiantian; Cao, Yongqing; Li, Chengfeng; Tian, Yong; Chen, Li; Li, Guoqin; Lu, Lizhi (Frontiers in Immunology, 2023)
This study was conducted to assess the effects of dietary supplementation of coated sodium butyrate (CSB) on the growth performance, serum antioxidant, immune performance, and intestinal microbiota of laying ducks. A total of 120 48-week-old laying ducks were randomly divided into 2 treatment groups: the control group (group C fed a basal diet) and the CSB-treated group (group CSB fed the basal diet + 250 g/t of CSB). Each treatment consisted of 6 replicates, with 10 ducks per replicate, and the trial was conducted for 60 days. Compared with the group C, the group CSB showed a significant increase in the laying rate (p <0.05) of the 53-56 week-old ducks. Additionally, the serum total antioxidant capacity, superoxide dismutase activity and immunoglobulin G level were significantly higher (p <0.05), while the serum malondialdehyde content and tumor necrosis factor (TNF)-α level were significantly lower (p <0.05) in the serum of the group CSB compared to the group C. Moreover, the expression of IL-1β and TNF-α in the spleen of the group CSB was significantly lower (p <0.05) compared to that of the group C. In addition, compared with the group C, the expression of Occludin in the ileum and the villus height in the jejunum were significantly higher in the group CSB (p <0.05). Furthermore, Chao1, Shannon, and Pielou-e indices were higher in the group CSB compared to the group C (p <0.05). The abundance of Bacteroidetes in the group CSB was lower than that in the group C (p <0.05), while the abundances of Firmicutes and Actinobacteria were higher in the group CSB compared to the group C (p <0.05). In summary, our results suggest that the dietary supplementation of CSB can alleviate egg-laying stress in laying ducks by enhancing immunity and maintaining the intestinal health of the ducks.